Usagi yojimbo (1996), volume 10 ebook The brink of life and death, 2nd edition. - Sakai, Stan (Usagi Yojimbo (1996), 2010)
While journeying over mountains, into valleys, through towns and farmlands, and along rugged coasts, searching for harmony, Usagi faces a unique cast of characters: a village of seaweed farmers, an innocent noodle peddler, a demon-possessed woman, a relentless clan of bat ninja, an assassins' guild, a mysterious medicine peddler, and Inazuma, a secretive female samurai. More than once Usagi finds himself in great danger — but it's all in a day's work when you walk the thin line on the brink of life and death.* Usagi Yojimbo: The Brink of Life and Death 2nd edition features completely remastered art and a look inside Stan Sakai's research and influences with new story notes! Includes an introduction by writer Kurt Busiek.